Konsep Kepemimpinan Rumah Tangga: Telaah Atas Pemikiran Asghar Ali Engineer - Siti Habibah Jazila (Justicia Islamica, 2006)
This study aims to examine the concept of household leadership in the perspective of Asghar Ali Engineer, a progressive Islamic thinker who highlights the issue of gender equality in Islam. Engineer interprets leadership in the household in an egalitarian manner, rejecting patriarchal domination, and emphasizing the principles of deliberation and justice between husband and wife. This study uses a qualitative method with a literature study approach, analyzing Engineer's works and her interpretation of verses from the Qur'an relating to household leadership. The results show that Engineer's concept of household leadership emphasizes cooperation and justice over an authoritative hierarchy. His perspective contributes to the modern discourse on gender roles in Muslim families. This study emphasizes that the interpretation of household leadership in Islam must consider the values of equality and justice in accordance with the spirit of maqashid sharia.